Електронне урядування в аграрному секторі економіки України - Застрожнікова, Ірина Володимирівна; Застрожникова, Ирина Владимировна; Zastrozhnikova, Iryna (My University, 2018)
UK: У статті досліджено основні аспекти електронного урядування в аграрній галузі економіки України. Розглянуто основні елементи електронного урядування аграрної сфери та їх можливості для агровиробників. Вивчено основні проблеми впровадження електронного урядування та визначено шляхи їх вирішення. EN: One of the most modern and promising forms of state regulation is e-government. Now e-governance is actively implemented in all sectors of the economy. At the moment, Ukraine needs a new agricultural policy that has a strategic and systemic character, social orientation, and consistent with the principles of sustainable development. The introduction of e-government in the agrarian sector of the Ukrainian economy is an important task of public administration.
Keywords: аграрні виробники; аграрна політика; аграрний сектор економіки; адміністративні послуги; державне регулювання; електронні ресурси; електронне урядування; інформаційні системи; е-уряд; agrarian producers; agrarian policy; agrarian sector of economy; administrative services; state regulation; electronic resources; e-government; information systems; agriculture; agricultural production